MAQASID AL-SHARIA IN ISLAMIC FINANCE - Solahuddin Al-Ayubi; Siti Halawatuddu'a (IAIN Bone, 2021)
Maqashid Shari'ah are general shari'ah goals and have an important role in conducting the study of Islamic laws. This study has several objectives, including first, to determine the definition, and function, to determine the role of maqashid shari'ah in concluding the law. Second, to find out the scholar's thoughts on maqasid shari'ah and various maqasid shari'ah. Third, to find out the implementation of maqashid shari'ah in Islamic social finance. This research uses normative juridical methods, namely legal research using secondary data sources, operationally normative juridical research is carried out by library research (Library Research). The result of the research is the scholar's thoughts on maqashid shari'ah can be divided into three stages, namely foundation, development, and contemporary. Maqasid shari'ah in Islamic social finance is to realize justice and welfare in society, and to realize the continuity human life on this earth.